The Use of Administrative Databases to Assess Oral Health Care - James L. Leake, MSc; Renata I. Werneck, DDS (Blackwell Synergy, 2005)
We examined the potential for research using administrative databases containing dentists’ claims to identify both the type of health services research questions addressed and the strength of the evidence that is achieved in such studies.